(untitled) (Journal of Information and Communication Technology, 2016)
The easy access and flexibility provided by cloud computing have made various types of organizations use this technology as an alternative solution. However, the decision to use the cloud technology sometimes ignores the basic aspects related to the understanding of its compliance with the characteristics of the organization. Thus, many advantages of the adoption of the technology do not align with the needs. This paper discusses the requirements engineering of the alignment of the organizational characteristics and the cloud computing technology in order to create the adaptive ability to guide strategic-business driven organizations. The model proposed in this article is formulated based on three views: architectural, alignment, and adaptive, by employing the Goal-Oriented Requirements Engineering. As a case study, the model is applied to cloud computing for university. The architectural view can translate the environmental characteristics of organizations through goal decomposition into detailed needs. Meanwhile, the alignment view can meet the implementation, so the dynamic adaptive ability can be realized through the adaptivity view.The mechanism of our proposed model can cover the adaptation needs before the migration (pre-migration), during the migration, and after the migration (post-migration).